Endotheliumprotectiv and antihypoxic properties of quercetin in elderly patients with metabolic syndrome - O. V. Korkushko; I. A. Antoniuk-Shcheglova; S. S. Naskalova; O. V. Bondarenko; O. M. Hryb; V. B. Shatylo; N. M. Koshel (Zaporožskij Medicinskij Žurnal)
Aim: To investigate the effectiveness of course quercetin in improving functional state of the microvascular endothelium and to determine the possibility of using quercetin to increase body resistance to hypoxia in the elderly.